2013
DOI: 10.2147/ijn.s38737
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of paclitaxel-loaded nanoparticles with a low-molecular-weight copolymer inhibitor of P-glycoprotein to overcome drug resistance

Abstract: Two types of nanoparticles were prepared using the diblock copolymer methoxy poly(ethylene glycol)-block-poly(caprolactone) (MePEG-b-PCL), with either a short PCL block length, which forms micelles, or with a longer PCL block length, which forms kinetically "frozen core" structures termed nanospheres. Paclitaxel (PTX)-loaded micelles and nanospheres were evaluated for their cytotoxicity, cellular polymer uptake, and drug accumulation in drug-sensitive (Madin-Darby Canine Kidney [MDCK]II) and multidrug-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Moreover, Xu et al demonstrated promising results obtained during treatment of drug-resistant A549 lung cancer cell with PLGA-based nanoparticles loaded with cyclosporin A and encapsulated P-gp inhibitor [ 139 ]. These observations are in great agreement with reports demonstrated in previous years [ 140 , 141 ].…”
Section: Nanoparticles-based Approaches To Reverse Multidrug Resistansupporting
confidence: 94%
“…Moreover, Xu et al demonstrated promising results obtained during treatment of drug-resistant A549 lung cancer cell with PLGA-based nanoparticles loaded with cyclosporin A and encapsulated P-gp inhibitor [ 139 ]. These observations are in great agreement with reports demonstrated in previous years [ 140 , 141 ].…”
Section: Nanoparticles-based Approaches To Reverse Multidrug Resistansupporting
confidence: 94%
“…Several mechanisms of resistance to taxanes have been described. Overexpression of drug efflux pumps, such as P-glycoprotein and multidrug resistance-associated protein-1 (MRP1), is one of the possible drug resistance mechanisms [15][16][17]. MRP1 can efficiently pump antineoplastic drugs out of cancer cells, thereby lowering intracellular drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…c and d). As demonstrated in previously published studies, after an initial incubation with PTX, it was essential to maintain the presence of MePEG 17 ‐b‐PCL 5 in the media to enable inhibition of P‐gp and hence retention of PTX within MDCKII‐MDR cells . Therefore, it is possible that after incubation with the cells and subsequent removal of the formulations, the concentration of MePEG 17 ‐b‐PCL 5 associated with the cells did not remain high enough to prevent efflux by P‐gp.…”
Section: Discussionmentioning
confidence: 96%
“…As demonstrated in previously published studies, after an initial incubation with PTX, it was essential to maintain the presence of MePEG 17 -b-PCL 5 in the media to enable inhibition of P-gp and hence retention of PTX within MDCKII-MDR cells. 38 Therefore, it is possible that after incubation with the cells and subsequent removal of the formulations, the concentration of MePEG 17 -b-PCL 5 associated with the cells did not remain high enough to prevent efflux by P-gp. In light of the results presented in Figure 5, it was apparent that long-term treatment with the P-gp inhibitor was required to inhibit the growth of MDCKII-MDR cells; therefore, we investigated the effect of continuous 3-day incubation of MDCKII-MDR cells with free drug or drug-loaded nanoparticles with varying concentrations of copolymer ( Fig.…”
Section: Cytotoxicity Of Mepeg-b-pcl Nanoparticulate Formulationsmentioning
confidence: 99%